2000
DOI: 10.1023/a:1005167917916
|View full text |Cite
|
Sign up to set email alerts
|

Subverting Culture: Promoting HIV/AIDS Prevention Among Puerto Rican and Dominican Women

Abstract: This article discusses the challenges faced by researchers and interventionists when attempting to promote change in social norms and normative beliefs that promote HIV/AIDS risk-related behaviors among Puerto Rican and Dominican women. The article focuses on the role of culture in HIV/AIDS prevention with women by analyzing the sociohistorical context of some cultural beliefs and by illustrating the tension between risk-related and protective cultural beliefs in research conducted by the authors with women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
(20 reference statements)
1
27
0
2
Order By: Relevance
“…In contrast, a number of different strategies were effective in increasing condom use among populations with lower percents of Latinos (i.e., attitudinal and behavioral skills arguments, information provision, condom use skills and self-management training, and HIV counseling and testing). We believe that this difference gives support to the contention that HIV prevention campaigns for the Latino population need to attend to culture (Marín et al, 1997;Ortiz-Torres et al, 2000). However, more research needs to be conducted to determine why threat-inducing arguments may be more effective among persons of Latino origin relative to other backgrounds.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, a number of different strategies were effective in increasing condom use among populations with lower percents of Latinos (i.e., attitudinal and behavioral skills arguments, information provision, condom use skills and self-management training, and HIV counseling and testing). We believe that this difference gives support to the contention that HIV prevention campaigns for the Latino population need to attend to culture (Marín et al, 1997;Ortiz-Torres et al, 2000). However, more research needs to be conducted to determine why threat-inducing arguments may be more effective among persons of Latino origin relative to other backgrounds.…”
Section: Discussionmentioning
confidence: 83%
“…With regards to the source of the intervention, we found that the use of lay community members did not increase condom use for groups with higher percents of Latinos/Latin Americans (even when gender was considered) and that groups with lower percents of Latinos/Latin Americans responded well to experts. This finding with regards to Latinos is worrisome considering the use of lay community members has been recommended for HIV prevention among Latinos (Center for AIDS Prevention Studies, University of California at San Francisco, 2002;Ortiz-Torres et al, 2000). However, the use of lay community members proved effective in increasing HIV related knowledge in groups with high percents of Latinos/Latin Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Although research suggests that sexual scripts are becoming more egalitarian, especially within steady relationships (Hynie and Lydon 1995;O'Sullivan and Byers 1992), this work has been criticized for its focus on samples that are predominantly White, more educated, and/or possess greater socioeconomic status (Metts and Spitzberg 1996;Ortiz-Torres et al 2000;Peplau 2003). Critics of sexual script research have argued that the impact of cultural factors on the individual expression of scripts remains largely unstudied (Ortiz-Torres et al 2000;Peplau 2003;Seal and Ehrhardt 2003;Seal et al 2000;Wyatt 1994). These authors suggest that women in relationships characterized by unequal power, economic disempowerment, and educational inequalities are more likely to submit to traditional gender roles (Amaro 1995;Ehrhardt et al 1992;Gomez and VanOss-Marin 1996;Ortiz-Torres et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…En el caso particular de Puerto Rico, estos cambios están relacionados por la transmisión de la infección por la vía de las relaciones heterosexuales sin protección (ídem). Hay estudios que demues-tran que la población femenina está en mayor riesgo de infección del VIH/SIDA que la masculina por algunos elementos biológicos (OlivaVenero, Saavedra-Ramírez, Viñas-Martínez, 2009), sociales y culturales (Ortíz, Serrano-García y Burgos-Torres, 2000).…”
Section: Discurso Patriarcal Y Vih/sida En Las Mujeres En Puerto Ricounclassified
“…Se ha documentado como el VIH/SIDA ha afectado desproporcionadamente a las mujeres en comparación con los hombres (Sepúlveda-Torres et al, 2012). Sin embargo, es limitado el análisis sobre cómo elementos de la cultura patriarcal pudieran ser perjudiciales para la salud e incidir en la vulnerabilización de estas con el VIH y su evolución a la enfermedad del SIDA (Ortiz, Serrano-García, Burgos-Torres, 2000). Este trabajo busca comprender cómo elementos del discurso patriarcal matizan los procesos de estigmatización en las mujeres que viven con VIH/SIDA y como ello pudiera incidir negativamente en el tratamiento de esta población.…”
Section: Introductionunclassified